Revealing the potential role of hsa-miR-663a in modulating the PI3K-Akt signaling pathway via miRNA microarray in spinal muscular atrophy patient fibroblast-derived iPSCs - Gandhi, Gayatri; Kodiappan, Radha; Abdullah, Syahril; Teoh, Hoon Koon; Tai, Lihui; Cheong, Soon Keng; Yeo, Wendy Wai Yeng (Oxford University Press, 2024)
Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder due to deletion or mutation of survival motor neuron 1 (SMN1) gene. Although survival motor neuron 2 (SMN2) gene is still present in SMA patients, the production of full-length survival motor neuron (SMN) protein is insufficient owing to missing or mutated SMN1. No current disease-modifying therapies can cure SMA. The aim of this study was to explore microRNA (miRNA)-based therapies that may serve as a potential target for therapeutic intervention in delaying SMA progression or as treatment. The study screened for potentially dysregulated miRNAs in SMA fibroblast-derived iPSCs using miRNA microarray. Results from the miRNA microarray were validated using quantitative reverse transcription polymerase chain reaction. Bioinformatics analysis using various databases was performed to predict the potential putative gene targeted by hsa-miR-663a. The findings showed differential expression of hsa-miR-663a in SMA patients in relation to a healthy control. Bioinformatics analysis identified GNG7, IGF2, and TNN genes that were targeted by hsa-miR-663a to be involved in the PI3K-AKT pathway, which may be associated with disease progression in SMA. Thus, this study suggests the potential role of hsa-miR-663a as therapeutic target for the treatment of SMA patients in the near future. © 2024 The Author(s).